2010
DOI: 10.1001/archgenpsychiatry.2009.205
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Hippocampal Subfields in Posttraumatic Stress Disorder

Abstract: Context Most neuroimaging studies of posttraumatic stress disorder (PTSD) have focused on potential abnormalities in the whole hippocampus, but the subfields of this structure, which have distinctive histological characteristics and specialized functions, have not been investigated. Studies of individual subfields may clarify the role of the hippocampus in PTSD. Objective To determine if PTSD is associated with structural alterations in specific subfields of the hippocampus. Design Case-control study. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
9
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 63 publications
12
202
9
6
Order By: Relevance
“…8 We echo the author's sentiments that it's not evident from our current study that administration of IGF-1 will improve insomnia or attenuate comorbid symptoms. However, since there was a positive association between sleep quality improvements and IGF-1 increases, which is also confi rmed by a recent Cochrane meta-analysis, 9 it may be a treatment intervention worth exploring.…”
Section: 7supporting
confidence: 51%
“…8 We echo the author's sentiments that it's not evident from our current study that administration of IGF-1 will improve insomnia or attenuate comorbid symptoms. However, since there was a positive association between sleep quality improvements and IGF-1 increases, which is also confi rmed by a recent Cochrane meta-analysis, 9 it may be a treatment intervention worth exploring.…”
Section: 7supporting
confidence: 51%
“…Previous functional imaging studies have demonstrated smaller hippocampal volumes in patients with depression and PTSD (Sheline, 2003;Campbell et al, 2004;Bonne et al, 2008;Wang et al, 2010). Hence, we determined whether stress-induced dendritic spine loss might also represent a biological marker for vulnerability to stress.…”
Section: Resultsmentioning
confidence: 94%
“…Individual differences in susceptibility to stress-related cognitive and morphological changes Patients with stress-related psychiatric disorders often display persistent cognitive dysfunction that lasts for many weeks or months after the traumatic event (McNally, 2006;Wang et al, 2010). To characterize the molecular basis of susceptibility and resistance to stress-related psychiatric disorders, we adopted an acute, unpredictable, and inescapable restraint tailshock stress paradigm that profoundly impairs hippocampus-dependent spatial tasks such as object location memory (OLM) in rodents (Howland and Cazakoff, 2010;Roozendaal et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Neurogenesis impairment has been reported in rodent stress-induced models of depression (Pham et al, 2003) and there are consistent reports of smaller dentate gyrus (DG) and cornu ammonis 3 (CA3) subfield volumes in patients with post-traumatic stress disorder, with sparing of other hippocampal subfields (Wang et al, 2010). Determinants of hippocampal volume in MDD are not known.…”
Section: Introductionmentioning
confidence: 99%